Categorization of anestrus in bovines belonging to marginal dairy farmers of Malwa region of Punjab - SINGH, JAGIR; HONPARKHE, M; DADARWAL, D; KUMAR, AJEET; CHEEDE, G S; KANG, R S (The Indian Journal of Animal Reproduction, 2023)
A field-oriented study was conducted to have an insight of various etiological factors of anestrus and their occurrence incattle and buffalo of Malwa region of Punjab. A total of I 16 animals (Cattle-58; Buffalo-58) with the history of anestrus weresubjected to gynaecological examination and diagnosis was made on the basis of history, clinical signs, rectal findings, body conditionscores (BCS) and plasma progesterone profiles. Repeated clinico-gynaecological examinations were made and plasma samples takenat 3-5 days interval for 21 days. Out of the total 58 cows presented, 37 (63.79%) were in true anestrus, 6 (10.34%) in subestnJs, I(1.72%) had persistent corpus luteurn and 14 (24.13%) were found pregnant, whereas the number of buffaloes in the respectivecategories were 12 (20.69%), 15 (25.86%), 2 (3.45%) and 29 (50.00%). The higher number of buffaloes diagnosed to have subestrusreflects the inadequacy of farming community to detect estrus properly as they consider the vocalization as sole criteria of estrus.Also the percentage of animals (both cattle and buffalo) diagnosed as pregnant (although presented to be of anestrus) point toward$the poor managerial skills of the farmers. Most of cows [20/37 (54.05%)] and buffaloes [10/12 (83.33%)) in true anestrus werepostpubertal heifers having a BCS ranging from 2.0-2.5.
Keywords: Anestrus; bovines; progesterone